The portrait of a prophet - why is Wright not right about Jesus? - Dannhauser, Estelle (HTS teologiese studies, 2008)
N T Wright’s extensive research on the subject of the historical Jesus has led him to the conclusion that the office of eschatological prophet passionately bent on delivering an urgent eschatological message is best suited to describe the portrait of Jesus as it emanates from the sources at hand. Wright furthermore abstracts from the sources the program of this prophet which involves extending a message of welcome and warning. Many a scholar would agree with these conclusions. When revealing how he arrived at the conclusions he refers to the “notorious” complexity of the problem of the literary relationship between the gospels. Can any scholar disagree? What does, however, seem to invite contention, are his statements that the gospels tell us far more about Jesus than scholarship has ever done, and that the two-source hypothesis which has been misleading scholars over the past two hundred years is not of any great importance in the study of Jesus. Wright believes that we are not in a position to answer the synoptic question and then bases a reconstruction of Jesus on this answer. What, then, are his sources and how does he apply them to arrive at these conclusions? This article presents the portrait Wright painted of the historical Jesus and investigates how it was arrived at.